Hair efficacy of botanical extracts. Issue 1 (18th July 2012) - Benaiges, Aurora; Fernández, Estibalitz; Martínez‐Teipel, Blanca; Armengol, Ricard; Barba, Clara; Coderch, Luisa
Abstract The great increase of capillary treatments (bleaching, perming, etc.) has created an important demand for hair cosmetics designed to repair and even prevent adverse effects on the capillary structure. In this work, the effect on hair of three botanical actives is investigated. Hair was chemically damaged by bleaching and the efficacy of three botanical actives was demonstrated by evaluation of surface morphology, differential scanning calorimetry, strength/relaxation, and absorption/desorption properties. Bleaching treatments have been demonstrated to modify the hair properties producing an increase in the fiber permeability and detrimental effects on the mechanical properties. Application of the botanical extracts to pretreated hair has improved the mechanical properties, giving rise to a reduction of the fibres' permeability, coating them and increasing the crystalline material of the fibers. Treatments with botanical actives based on either proteins and peptides, sulfated polysaccharides or a combination of polysaccharides could be used to protect and repair the hair fibers. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013